2023
DOI: 10.1371/journal.pcbi.1010874
|View full text |Cite
|
Sign up to set email alerts
|

Funneling modulatory peptide design with generative models: Discovery and characterization of disruptors of calcineurin protein-protein interactions

Abstract: Design of peptide binders is an attractive strategy for targeting “undruggable” protein-protein interfaces. Current design protocols rely on the extraction of an initial sequence from one known protein interactor of the target protein, followed by in-silico or in-vitro mutagenesis-based optimization of its binding affinity. Wet lab protocols can explore only a minor portion of the vast sequence space and cannot efficiently screen for other desirable properties such as high specificity and low toxicity, while i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…1 ). It has previously been demonstrated that the incorporation of free cysteines in peptides increases tumor accumulation by forming disulfide bonds to serum albumin rather than a specific receptor-ligand interaction; therefore, we only selected miniprotein sequences without cysteines ( SI Appendix , Table S3 ) ( 27 ). Although some of the eight selected miniproteins have homologous sequences, AlphaFold2 predictions revealed unique 3D conformations, surface hydrophobic networks, and surface charge distributions ( Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). It has previously been demonstrated that the incorporation of free cysteines in peptides increases tumor accumulation by forming disulfide bonds to serum albumin rather than a specific receptor-ligand interaction; therefore, we only selected miniprotein sequences without cysteines ( SI Appendix , Table S3 ) ( 27 ). Although some of the eight selected miniproteins have homologous sequences, AlphaFold2 predictions revealed unique 3D conformations, surface hydrophobic networks, and surface charge distributions ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, incorporating more rational design into both library design and in vivo selection strategy could further decrease the number of rounds of selection needed to achieve a desired result and further improve the quality of the molecules identified. For example, designing more complex surface libraries or miniprotein binder libraries against specific targets is now possible using cutting-edge machine learning-based design methods and would enable the in vivo library selection strategy to be tailored to those targets ( 27 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The excited fluorescent probe (i.e., SAT peptide) bound to a large molecular weight protein (i.e., OASS) emits light with a degree of polarization that is inversely proportional to the rate of molecular rotation. This fluorescence property is exploited to measure the interaction of a small labeled ligand with a larger protein and provides a basis for direct and competition binding assays 29,30 . Herein, we relied on the known SAT-derived peptide YLTEWSDYVI (SATp) conjugated with fluorescein isothiocyanate (FITC).…”
Section: Screening the In-vitro Binding Of Selected Virtual Hits By F...mentioning
confidence: 99%